Atlas of clinical gastrointestinal endoscopy - Wilcox, C. Mel (Elsevier/Saunders, 2012)
Provides high-quality images than any other atlas to help you accurately interpret endoscopic images and diagnose gastrointestinal disorders. This title covers radiographic imaging and endoscopic evaluation methods and features an expanded image collection that includes more pathology and radiology images.